Compensation claims for occupational noise induced hearing loss between 1998 and 2008: yearly incidence rates and trends in older workers - Samia Radi; Geza Benke; Frederieke Schaafsma; Malcolm Sim (Australian and New Zealand Journal of Public Health, 2016)
Abstract Objectives: To estimate yearly incidence rates for occupational noise induced hearing loss (ONIHL) claims and to describe occupational factors in relation to age for incident cases in Victoria, Australia, between 1998 and 2008. Methods: All compensation claims lodged for deafness between 1 July 1998 and 30 June 2008 in the working population covered by the Victorian compensation scheme were analysed. Denominators were provided from 1999–2000 and incidence rates were expressed per 100,000 workers for each financial year. Results: Overall, 81.2% of the 4,518 claims lodged were accepted. Successful claimants were predominantly males (96.5%) and claimants aged 56 to 65 years formed half the overall claims. The number of accepted claims was almost five times higher in 2007–08 than 1998–99. The highest rise was in claimants aged 56 years and above, particularly in those after retirement age. The number of claims and yearly incidence rates (IR) more than doubled over the period (240 claims and IR of 15.1 per 100,000 workers in 1999–2000 versus 669 claims and IR of 34.2 in 2007–08) with a sharp increase from 2004–05 to almost double within one single year and remained at high levels afterwards. Conclusion: The dramatic increase in eligible claims may reflect an increase in awareness of entitlements among workers eligible to make a successful claim. This awareness may be the result of increased opportunities for screening coinciding with changes in regulations. Older workers who worked in smaller workplaces may also be targeted by services providers as they combine occupational noise induced hearing loss (ONIHL) and presbycusis (hearing loss due to age), but this hypothesis needs further evaluation.